An analysis on vocabulary errors in the written English of Malay students at Sekolah Menengah Rusila, Marang, Terengganu / Jusoh Ismail - Ismail, Jusoh (2002)
The main aim of the thesis is to investigate the errors most Malay students make in their written compositions ..The error analysis will be focused on the lexical errors or vocabulary errors . The findings of the investigation are based on the 60 selected samples (at random) among the form five students of Sekolah Menengah Kebangsaan Rusila in the rural area of Marang.Terengganu. Chapter One begins with the Introduction . A review of related literature on the use of Error Analysis as the medium of investigating vocabulary errors is discussed in Chapter Two. Chapter Three deals with the research design and methodology of the study undertaken for the present study. Chapter Four focuses on several findings and the presentation of that findings The Final Chapter highlights Summary, Conclusion and several recommendations.